Editorial Problems of Organizing the Innovative Activity of Preschool Education Organization Editors Under Educational Cluster Conditions - Zulfiya Karimova (Euro Asian Journal Publishing, 2023)
This article talks about the organization of innovative activities of preschool education pedagogues in the context of an educational cluster. The researches of scientists about the concepts of cluster, educational cluster, innovation, educational innovations are widely studied, and a point of view is shown regarding the conclusions obtained from them
Keywords: cluster; system; systemtechnology